Simulation and Modeling-Based Refinery Hydrogen Network Integration with Process Risk Analysis - Zhang, Qiao; Fang, Qing; Feng, Xiao (Industrial & engineering chemistry research, 2021)
Hydrogen network integration is a crucial way to achieve resource conservation and cost reduction of refinery and it is performed on quantitative and thermodynamic properties of hydrogen streams subject to process operation and thermodynamic principles. A combined methodology of process simulation and mathematical modeling is optimal to account for process operation and integration of hydrogen networks. In this paper, process simulation of a flash separator is employed to obtain quantitative and thermodynamic properties of hydrogen streams under variational flash pressure (FP), and a mixed-integer nonlinear programming model is established to minimize the total exergy of hydrogen networks. A practical refinery case with different-quality crude oil is investigated, and the results indicate that flash pressure is the risk factor and should be in the feasible region no larger than the process operation and no less than the critical level for integration. Quantitatively, the critical level of FP for high-pressure sk1 is 17.42 MPa and will be increased to 17.57 MPa by inferior crude oil and decreased to 16.76 MPa by superior oil feedstock. Similarly, in the case of sk4, it is 6.14 MPa and increased to 6.29 MPa and decreased to 5.52 MPa. As a result, the crude oil feed of sk4 in case 2 is in the risk region already, and flash pressure should be adjusted. This work shows great progress in hydrogen network integration with risk analysis for future applications.